1996
DOI: 10.1159/000262350
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring De- and Remineralisation of Enamel in vitro Using an Infrared Reflectance Meter

Abstract: The aim of this study was to design and investigate the use of an inexpensive method of monitoring the progress of demineralisation and subsequent remineralisation in artificial carious lesions. A small infrared (IR) reflectance meter was built which illuminated a 4 mm×4 mm area on the buccal surface of a tooth and measured the reflected IR intensity. Repeated measurements were taken over a period of 25 days, during which the enamel surface was exposed to demineralising and subsequently remineralising solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The increase in scattered radiation will be at the expense of light transmitted into the enamel and light specularly reflected. The present results are therefore also consistent with earlier studies [Vaarkamp et al, 1995;Anderson et al, 1996] in which a reduction in specular reflection was observed with increased demineralization. Note that unlike the R a values, the increase in reflectivity is not linear with time, but appears to be a saturating exponential change as was reported by Anderson et al [1996] for infrared specular reflection.…”
Section: Main Experimentssupporting
confidence: 94%
“…The increase in scattered radiation will be at the expense of light transmitted into the enamel and light specularly reflected. The present results are therefore also consistent with earlier studies [Vaarkamp et al, 1995;Anderson et al, 1996] in which a reduction in specular reflection was observed with increased demineralization. Note that unlike the R a values, the increase in reflectivity is not linear with time, but appears to be a saturating exponential change as was reported by Anderson et al [1996] for infrared specular reflection.…”
Section: Main Experimentssupporting
confidence: 94%
“…IR reflectance measurements of 9 test and 9 control teeth were based on the method detailed by Anderson et al . [24] in a study, which showed that the IR reflectance of caries and opacity free molars decreased during demineralisation, and increased during remineralisation. In the present study, an IR reflectance meter was used to record the change in IR reflected intensity before and after pumicing and acid etching, and during exposure to the remineralising solution.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, a method that enables nondestructive time-dependent monitoring of one and the same specimen is another example of increase of information. Replacement of destructive methods, like microhardness and histology, with non-destructive methods is common in caries research [14][15][16]. Validation then should be done against the final situation, determined either clinically or by histology [16].…”
Section: Validation Of a Methods That Is Expected To Be 'Better' Than mentioning
confidence: 99%